Increasing the Productivity of Rice Fields with the Mina Sari Cultivation Technique in Kenderan Village, Tegallalang District, Gianyar Regency - Dicky Marsadi; I Kadek Ayu Charisma Julia Dewi; I Wayan Dirgayana (Journal of Sustainable Development Science, 2024)
cultivation techniques with mina padi cultivation techniques. This study aims to increase the productivity of rice fields in Kenderan Village, Tegallalang District, Gianyar Regency. The research method used is the experimental method with Randomized Block Design (RAK) with 2 treatments. Data analysis in this study used descriptive analysis, quantitative analysis and farming business analysis. The results of the study showed that the mina sari cultivation technique was able to produce 3 types of commodities with gonda plant production of 1,760 kg/ha, rice plants 6,780 kg/ha, and tilapia fish as much as 1,390 kg/ha. The sales results from all commodities allow farmers to earn an income of IDR 83,300,000 per hectare. Monoculture system, rice fields are only able to produce rice plants with a yield of 7,334 kg/ha. The rice yield obtained from the monoculture technique is slightly higher than the Mina Sari technique, the income from farmer sales with the monoculture system is much lower, which is IDR 44,004,000 per hectare. The results of the R/C analysis showed a value of 2.02 in the Mina Sari cultivation technique and a value of IDR 2.47 in monoculture. The R/C value in farming with the Mina Sari and monoculture cultivation techniques showed a value> 1 so that both cultivation techniques were profitable.